Business intelligence : from conventional to cognitive (2019)
Technological systems enhance organizations since 1958 and are the ground basis of a strong managerial operation in today´s business competition. Based on a literature review that identifies past, present and future applications of technology from business intelligence to artificial intelligence. This article offers an understanding of which technological advances are applied in organizations to adapt and survive within an ever-changing environment in business world today. Business intelligence´s definition and key divisions are described to carry on a wide explanation due to its scope. Based in a state-of-the-art literature revision and going through several definitions, BI it is analyzed as a process and as technological aid. From key divisions in its application such as: reporting, analysis, monitoring and prediction to its extensions based on time frames in operational and strategic bids. BI is the starting point to excel why having a decision support making tool is key to hedge the risk from failure to be an outstanding tool to increase profits. How can systems create for themselves prediction modules that optimize and later adapt to future scenarios based on historic data and how its adaptivity is key. Therefore, new technologies are emerging at a neck breaking speed. Hence, this article explains and help to understand their scope and importance within the world we live in and why companies must innovate and cope with them when building their industry to new horizons. Internet of things, machine learning and artificial intelligence are the new emerging and disruptive technologies that are being implemented in all industries creating new trends and challenges to manage.